DAMPAK PANDEMI COVID TERHADAP PEMBELAJARAN DARING MATA PELAJARAN PAI - Novia, Washilatun; Wasehudin, Wasehudin (TARBAWY : Indonesian Journal of Islamic Education, 2021)
Abstract. This study aims to analyze the impact of the COVID-19 pandemic on the implementation of online learning of Islamic Religious Education (IRE) in elementary schools. By using the literature study method, this study found that the COVID-19 pandemic had a positive and negative impact on the implementation of online learning in elementary schools. The impact is experienced by students, parents, teachers, and has an impact on learning itself. On the positive side, online learning can prevent transmission of the virus to other people, the learning atmosphere at home for students can be more conducive, parents can increase their time together with children, teachers can improve digital literacy skills, and learning can be more varied. On the other hand, online learning has the opportunity to widen the gap between students in rural areas and students in urban areas due to differences in facilities, parents’ educational background, internet access and technology.Abstrak. Penelitian ini bertujuan untuk menganalisis dampak pandemi covid-19 terhadap penyelenggaraan pembelajaran daring Pendidikan Agama Islam (PAI) di Sekolah Dasar. Dengan menggunakan metode studi kepustakaan, penelitian ini menemukan pandemi covid-19 memberikan dampak yang positif dan negatif terhadap implementasi pembelajaran daring di lingkup Sekolah Dasar. Dampak tersebut dialami oleh siswa, orang tua, guru, dan berdampak pada pembelajaran itu sendiri. Pada sisi positif, pembelajaran daring dapat mencegah penularan virus ke orang lain, suasana belajar di rumah bagi siswa dapat lebih kondusif, orang tua dapat menambah waktu kebersamaannya dengan anak, guru mampu meningkatkan kemampuan literasi digital, dan pembelajaran dapat lebih variatif. Pada sisi lain, pembelajaran daring berpeluang untuk memperlebar kesenjangan yang terjadi antara siswa di perdesaan dengan siswa di perkotaan karena perbedaan fasilitas, latar belakang pendidikan orang tua, akses internet dan teknologi.